Time-of-day effects on biochemical responses to soccer-specific endurance in elite Tunisian football players - Hammouda, O.; Chtourou, H.; Chaouachi, A.; Chahed, H.; Bellimem, H.; Chamari, K.; Souissi, N. (Journal of Sports Sciences, 2013)
This study aimed to investigate footballers` diurnal variation of performance during the Yo-Yo intermittent recovery test and the associated biochemical responses. Fifteen male footballers (17.3 ± 0.3 years, 69.1 ± 4.2 kg, 179.7 ± 3.6 cm) performed two randomised Yo-Yo tests at 07:00 h and 17:00 h. Blood samples were collected before and 3 min after each test for the assessment of metabolic responses. Resting oral temperature and rating of perceived exertion (RPE) after and peak heart rate during the Yo-Yo test were recorded at both times-of-day. Core temperature and performances during the Yo-Yo test increased from the morning to the evening (P < 0.0005 and P = 0.01, respectively) without significant time-of-day effects on peak heart rate and RPE. Moreover, pre- and post-Yo-Yo test biochemical parameters (high-density lipoprotein, triglycerides, glucose, creatine-kinase) were higher at 17:00 h than 07:00 h (160.45 ± 18.68 vs. 173.73 ± 14.48 before and 191.18 ± 21.13 vs. 219.27 ± 27.74 IU/L after the Yo-Yo test at 07:00 h and 17:00 h, P = 0.032 and P < 0.0005, respectively for creatine-kinase). Only post-exercise lactate levels were higher in the evening (9.82 ± 0.65 vs. 10.86 ± 0.33 mmol/L, P < 0.0005) with all biochemical variables being increased after the exercise (P < 0.0005). These findings suggest a possible link between the diurnal fluctuation of metabolic responses and the related pattern of specific-endurance performances in footballers. Therefore, the higher biochemical responses observed in the evening could explain, partially, the greater performance and metabolic solicitation at this time-of-day.